General ledger accounting with SAP S/4HANA - Seetharaju, Anand (Rheinwerk Publishing, 2023)
"The general ledger is the backbone of your financials system. Learn everything you need for configuring and using the general ledger in SAP S/4HANA. Walk step by step through setting up fiscal years, posting periods, parallel ledgers, and more. See routine processes like posting, document control, and year-end closing in action. Whether you're planning a new implementation or a system conversion, this is your complete guide to general ledger accounting in SAP S/4HANA!"--